Pergerakan Islam Modern dan Transformasi Pendidikan Nasional:Analisis Historis dan Konseptual - Vindia Putri; Isma Yuliza (CV. ITTC INDONESIA, 2025)
This study aims to analyze the contribution of the modern Islamic movement to the transformation of Indonesia’s national education through a historical and conceptual approach. Islamic modernism that developed since the 19th century, through figures such as al-Afghani, Abduh, and Rasyid Ridha, had a significant influence on Nusantara scholars who later applied its reformist ideas in Indonesia. Organizations such as Muhammadiyah, Al-Irsyad, and Persis became instruments for disseminating modernism through the development of modern educational institutions, the strengthening of rationality, and the integration of religious and general sciences. Historical studies show that the concept of modern education introduced by modernist movements helped shape the direction of national education policy from the early independence period to the Merdeka Belajar era. Meanwhile, the conceptual analysis reveals that the transformation of national education cannot be separated from social dynamics and the development of global pedagogical paradigms that emphasize flexibility, character, digital literacy, and student-centered learning. The results of this study affirm that the dialogue between the values of Islamic renewal and the needs of modernity has produced a national education pattern that is adaptive, rational, and relevant to the challenges of the 21st century. These findings are important as a basis for developing educational policies that integrate spirituality, rationality, and the advancement of scientific knowledge.